Agathisflavone Inhibits Viability and Modulates the Expression of miR-125b, miR-155, IL-6, and Arginase in Glioblastoma Cells and Microglia/Macrophage Activation - Karina Costa da Silva; Irlã Santos Lima; Cleonice Creusa dos Santos; Carolina Kymie Vasques Nonaka; Bruno Solano de Freitas Souza; Jorge Mauricio David; Henning Ulrich; Ravena Pereira do Nascimento; Maria de Fátima Dias Costa; Balbino Lino dos Santos; Silvia Lima Costa (Molecules)
Glioblastomas (GBM) are malignant tumours with poor prognosis. Treatment involves chemotherapy and/or radiotherapy; however, there is currently no standard treatment for recurrence, and prognosis remains unfavourable. Inflammatory mediators and microRNAs (miRNAs) influence the aggressiveness of GBM, being involved in the communication with the cells of the tumour parenchyma, including microglia/macrophages, and maintaining an immunosuppressive microenvironment. Hence, the modulation of miRNAs and inflammatory factors may improve GBM treatments. In this study, we investigated the effects of agathisflavone, a biflavonoid purified from Cenostigma pyramidale (Tul.), on the growth and migration of GBM cells, on the expression of inflammatory cytokines and microRNAs, as well on the response of microglia. Agathisflavone (5–30 μM) induced a dose- and time-dependent reduction in the viability of both human GL-15 and rat C6 cells, as determined by the MTT test, and reduced cell migration, as determined by cell scratch assay. RT-qPCR analysis revealed that agathisflavone (5 μM) down-regulated the expression of miR-125b and miR-155 in the secretome derived from GL-15 cells, which was associated with upregulation of the mRNA expression of IL-6 and arginase-1 immunoregulatory factors. Exposure of human microglia/macrophage to the secretome from GL-15 GMB cells modulated proliferation and morphology, effects that were modulated by agathisflavone treatment. These results demonstrate the effect of flavonoids on the growth of GBM cells, which impacts cells in the microenvironment and can be considered for preclinical studies for adjuvant treatments.